2022
DOI: 10.1108/imds-08-2021-0485
|View full text |Cite
|
Sign up to set email alerts
|

Revealing or concealing: privacy information disclosure in intelligent voice assistant usage- a configurational approach

Abstract: PurposeBased on communication privacy management (CPM) theory, this study aimed to explore how gender and age criteria, motivational criterion (locatability), benefit-risk ratio criteria (perceived benefits of privacy information disclosure and privacy concerns), contextual criteria (privacy experience) and boundary coordination and turbulence (perceived effectiveness of privacy policy) interact and combine in leading to voice assistant (VA) users' intention to reveal or conceal their privacy information.Desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
(142 reference statements)
1
7
0
1
Order By: Relevance
“…Even though Kim et al (2019) identified factors influencing the willingness to provide privacy information, they did not include the effect of attitude on willingness to provide personal information. Shortly thereafter, Cao and Wang (2022) called for research investigating other potential drivers (except privacy concerns) that could impact information disclosure but excluded privacy concerns. However, both attitudes towards using voice assistants and willingness to provide personal information were examined in this study and found to have a significant positive effect on engagement with using voice assistants.…”
Section: Discussion Conclusion and Future Researchmentioning
confidence: 99%
“…Even though Kim et al (2019) identified factors influencing the willingness to provide privacy information, they did not include the effect of attitude on willingness to provide personal information. Shortly thereafter, Cao and Wang (2022) called for research investigating other potential drivers (except privacy concerns) that could impact information disclosure but excluded privacy concerns. However, both attitudes towards using voice assistants and willingness to provide personal information were examined in this study and found to have a significant positive effect on engagement with using voice assistants.…”
Section: Discussion Conclusion and Future Researchmentioning
confidence: 99%
“…Dalam konteks sosial media, Nemec Zlatolas et al (2019) menjelaskan bahwa berdasarkan teori CPM, pengguna sosial media harus dapat mengontrol siapa yang dapat mengakses informasi yang mereka bagikan; dengan demikian, hal tersebut akan memengaruhi cara mereka mengungkapkan diri di platform sosial media. Cao & Wang (2022) mengeksplorasi bagaimana kriteria jenis kelamin dan usia, kriteria motivasi (locatability), kriteria rasio manfaat-risiko (persepsi manfaat dari pengungkapan informasi privasi dan masalah privasi), kriteria kontekstual (pengalaman privasi) dan koordinasi batas serta turbulensi (persepsi efektivitas kebijakan privasi) berinteraksi dan bergabung dalam mengarah ke niat pengguna untuk mengungkapkan atau menyembunyikan informasi privasi mereka. Laitinen & Sivunen (2020) menjelaskan pada platform media sosial perusahaan terdapat tiga dimensi, yakni pribadi, teknologi, dan organisasi, membentuk model yang memungkinkan dan membatasi keputusan karyawan untuk berbagi informasi di media sosial perusahaan dimana batasan privasi pribadi, batasan profesional dan asumsi risiko, masalah keamanan online menentukan keputusan berbagi informasi.…”
Section: Pendahuluanunclassified
“…Information privacy, defined as the control that individuals have over their personal data (Westin, 1967;Campbell, 1997), has been primarily studied in the context of direct marketing rather than online channels (Cao & Wang, 2022). However, the interactive nature of the Internet increases privacy risks (Malhotra et al, 2004;Sheehan & Hoy, 2000).…”
Section: 1information Privacy and Vapasmentioning
confidence: 99%
“…The advent of AI, particularly Voice-Activated Personal Assistants (VAPAs), has further complicated privacy issues. These devices rely on extensive personal and contextual data to function (Cao & Wang, 2022). Massara (2021) noted that two-thirds of Europeans are concerned about the lack of information control.…”
Section: 1information Privacy and Vapasmentioning
confidence: 99%
See 1 more Smart Citation